Attitudes of Consumers from the Sarajevo Canton in Bosnia and Herzegovina toward Advertising through Sport among the Frequency of Watching Sports Events - Izet Bajramovic; Gorica Zoric; Bojan Masanovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
It is proposed that potential consumers form attitudes based on advertising through sport can influence decisions to purchase a particular advertiser's product. From this reason, it is important to analyse their general attitudes toward advertising through sport among various questions, and this investigation was aimed at gaining relevant knowledge about the attitudes of Sarajevo consumers toward advertising through sport among. The sample included 358 respondents, divided into six subsample groups: consumers, who do not watch sports events at all, then consumers who watch sports events 1-30 minutes, next 31-60 minutes, 61-90 minutes, 91-120 minutes, as well as consumers who watch sports events more than 120 minutes during the typical day. The sample of variables contained the system of three general attitudes which were modelled by seven-point Likert scale. The results of the measuring were analysed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test. Based on the statistical analyses it was found that significant differences occur at multivariate level, as well as between all three variables at a significance level of p=.00. Hence, it is interesting to highlight that it was found there are significant differences showed up between the attitudes of consumers toward advertising through sport among the frequency of watching sports events. These results are so important for the marketers, mostly due to the reason they can't merge all the potential consumers regarding the frequency they watch the sports events. On the other hand, this is the case in previous investigations and this observation presents relevant information.